Applied Spatial Data Analysis Technique on Petrophysical Properties of MA Unit of Mishrif Formation / Noor Field - Baker, Hussain Ali; AL-Jawad, Sameer Noori; Abdulla, Aseel Ali (Iraqi Journal of Chemical and Petroleum Engineering, 2016)
Noor oil field is one of smallest fields in Missan province. Twelve well penetrates the Mishrif Formation in Noor field and eight of them were selected for this study. Mishrif formation is one of the most important reservoirs in Noor field and it consists of one anticline dome and bounded by the Khasib formation at the top and the Rumaila formation at the bottom. The reservoir was divided into eight units separated by isolated units according to partition taken by a rounding fields.In this paper histograms frequency distribution of the porosity, permeability, and water saturation were plotted for MA unit of Mishrif formation in Noor field, and then transformed to the normal distribution by applying the Box-Cox transformation algorithm. The spatial correlation of the transformed parameters were estimated and modeled in appropriate equation, and then the spatial distribution of the reservoir parameters were specified through Geostatistical methods.